Worsening urban ozone pollution in China from 2013 to 2017 – Part 2: The effects of emission changes and implications for multi-pollutant control - Liu, Yiming; Wang, Tao (Atmospheric chemistry and physics, 2020)
The Chinese government launched the Air Pollution Prevention and Control Action Plan in 2013, and various stringent measures have since been implemented, which have resulted in significant decreases in emissions and ambient concentrations of primary pollutants such as SO2, NOx, and particulate matter (PM). However, surface ozone (O3) concentrations have still been increasing in urban areas across the country. In a previous analysis, we examined in detail the roles of meteorological variation during 2013–2017 in the summertime surface O3 trend in various regions of China. In this study, we evaluated the effect of changes in multi-pollutant emissions from anthropogenic activities on O3 levels during the same period by using an up-to-date regional chemical transport model (WRF-CMAQ) driven by an interannual anthropogenic emission inventory. The Community Multiscale Air Quality (CMAQ) model was improved with regard to heterogeneous reactions of reactive gases on aerosol surfaces, which led to better model performance in reproducing the ambient concentrations of those gases. The model simulations showed that the maximum daily 8 h average (MDA8) O3 mixing ratio in urban areas increased by 0.46 ppbv per year (ppbv a−1) (p=0.001) from 2013 to 2017. In contrast, a slight decrease in MDA8 O3 by 0.17 ppbv a−1 (p=0.005) in rural areas was predicted, mainly attributable to the NOx emission reduction. The effects of changes in individual pollutant emissions on O3 were also simulated. The reduction of NOx emission increased the O3 levels in urban areas due to the nonlinear NOx and volatile organic compound (VOC) chemistry and decreasing aerosol effects; the slight increase in VOC emissions enhanced the O3 levels; the reduction of PM emissions increased the O3 levels by enhancing the photolysis rates and reducing the loss of reactive gases on aerosol surfaces; and the reduction of SO2 emissions resulted in a drastic decrease in sulfate concentrations, which increased O3 through aerosol effects. In contrast to the unfavorable effect of the above changes in pollutant emissions on efforts to reduce surface O3, the reduction of CO emissions did help to decrease the O3 level in recent years. The dominant cause of increasing O3 due to changes in anthropogenic emissions varied geographically. In Beijing, NOx and PM emission reductions were the two largest causes of the O3 increase; in Shanghai, the reduction of NOx and increase in VOC emissions were the two major causes; in Guangzhou, NOx reduction was the primary cause; in Chengdu, the PM and SO2 emission decreases contributed most to the O3 increase. Regarding the effects of decreasing concentrations of aerosols, the drop in heterogeneous uptake of reactive gases – mainly HO2 and O3 – was found to be more important than the increase in photolysis rates. The adverse effect of the reductions of NOx, SO2, and PM emissions on O3 abatement in Beijing, Shanghai, Guangzhou, and Chengdu would have been avoided if the anthropogenic VOCs emission had been reduced by 24 %, 23 %, 20 %, and 16 %, respectively, from 2013 to 2017. Our analysis revealed that the NOx reduction in recent years has helped to contain the total O3 production in China. However, to reduce O3 levels in major urban and industrial areas, VOC emission controls should be added to the current NOx-SO2-PM policy.